2013
DOI: 10.1177/014556131309200622
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Choriocarcinoma: A Rare Presentation as a Neck Mass

Abstract: Testicular carcinoma metastatic to the neck is rare. Even more rare is a finding of choriocarcinoma as a neck mass without any sign of a primary testicular tumor, as only a few cases have been reported in the literature. We describe a new case that occurred in a 29-year-old man who presented with a neck mass. Fine-needle aspiration biopsy identified the tumor as a malignant epithelial neoplasm. Radiologic findings indicated the presence of a systemic metastasis of a tumor to the chest and abdomen, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The overall incidence of malignant metastasis to the skin is between 1-and 4% [ 13 ]. There are some case reports of testicular or non-gestational choriocarcinoma metastasizing to the skin [ 14 17 ] but to the best of our knowledge, there are only eleven cases of GTN with meta-static skin lesions have been reported in the English language [ 10 , 11 , 13 , 18 24 ] ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of malignant metastasis to the skin is between 1-and 4% [ 13 ]. There are some case reports of testicular or non-gestational choriocarcinoma metastasizing to the skin [ 14 17 ] but to the best of our knowledge, there are only eleven cases of GTN with meta-static skin lesions have been reported in the English language [ 10 , 11 , 13 , 18 24 ] ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 Lauro et al have described stomach tumor when patients presented with a chief complaint of hematemesis. 11 Vardaros et al reported a case of duodenal metastasis from choriocarcinoma, 12 and Senkal et al 13 and Ahmadi et al 14 have independently reported cases of neck masses as the primary presentation in cases of testicular choriocarcinoma. Toberer et al reported a case of cutaneous metastasis from underlying choriocarcinoma, in which the patient had an extremely high disease load and died within 9 days of treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Extragonadal non-gestational midline ChC is a malignant, germ cell tumor composed of extraembryonic chorion that includes cytotrophoblastic and syncytiotrophoblastic cells, representing an incidence of 0.0022 per 1,000,000 people [6]. There are a few case reports of extragonadal midline ChC metastasizing to cervical lymph nodes [15], but to date, an oropharyngeal extragonadal nongestational ChC has not been reported.…”
Section: Introductionmentioning
confidence: 99%